2021
DOI: 10.1111/iju.14601
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pembrolizumab with conventional chemotherapy after first‐line platinum‐based chemotherapy for advanced urothelial carcinoma in real‐world practice: A multicenter retrospective study

Abstract: Objectives: To assess the clinical benefit of pembrolizumab as second-line therapy for advanced urothelial carcinoma. Methods: We retrospectively compared the effects of pembrolizumab with those of conventional chemotherapy on the prognosis of patients with advanced urothelial carcinoma at six hospitals between January 2004 and August 2020. We compared the oncological outcomes between the patients treated with pembrolizumab and those treated with conventional chemotherapy using Kaplan-Meier curve analysis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 29 publications
(41 reference statements)
2
27
0
Order By: Relevance
“…There is a lack of studies investigating the effects of the concomitant use of PPI or Abs and ICIs on irAEs. As many reports suggested a positive association between the efficacy and immune‐related AEs, 6,30 we speculate that the concomitant use of PPI or Abs may reduce the incidence of irAEs in conjunction with attenuated therapeutic effects. However, we observed no significant association of the concomitant use of PPI or Abs with the incidence of irAEs.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…There is a lack of studies investigating the effects of the concomitant use of PPI or Abs and ICIs on irAEs. As many reports suggested a positive association between the efficacy and immune‐related AEs, 6,30 we speculate that the concomitant use of PPI or Abs may reduce the incidence of irAEs in conjunction with attenuated therapeutic effects. However, we observed no significant association of the concomitant use of PPI or Abs with the incidence of irAEs.…”
Section: Discussionmentioning
confidence: 76%
“…Locally advanced or metastatic urothelial carcinoma (UC) is a life‐threatening disease with a poor prognosis. 1 , 2 , 3 Although immune checkpoint inhibitors (ICIs) have significantly impacted treatment strategies in UC in both clinical trials and real‐world practice, 4 , 5 , 6 , 7 , 8 the heterogeneity of treatment responses and outcomes is a major problem. 9 , 10 , 11 Proton pump inhibitors (PPIs) are common chronic medications used for gastroesophageal reflux and/or peptic ulcers.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies have analyzed and reported survival rates from the date of ICI initiation. [2][3][4][5][6]16 The pivotal trial, KEYNOTE-045, reported that median OS in the pembrolizumab group was 10.3 months as compared to 7.4 months in the chemotherapy group (P = 0.002), resulting in a 2.9-month survival benefit from the initiation of pembrolizumab or investigator's choice of chemotherapy. A recent report from the Japan Urological Oncology Group demonstrated a positive correlation between response to pembrolizumab and response to chemotherapy, 16 implying that time-totreatment failure of first-line chemotherapy is closely associated with that of second-line ICI therapy.…”
Section: Discussionmentioning
confidence: 99%
“…2 Recently, real-world data have presented oncological benefits and acceptable toxicity profiles of second-line or later pembrolizumab. [3][4][5][6] However, management of aUC is still challenging due to the heterogeneity of patient population; the optimization of the treatment sequence is needed to achieve a durable response and prolonged survival.…”
Section: Introductionmentioning
confidence: 99%
“…If PD or intolerable adverse events occurred, the first‐line treatment regimen was discontinued and switched to second‐line treatment regimens. 16 Given that the standard second‐line regimen was not yet defined before 2018 (pre‐pembrolizumab era), some patients were continuously treated with the first‐line therapy beyond PD. Our regimens for salvage chemotherapy included docetaxel‐based regimes (e.g., docetaxel + ifosfamide + nedaplatin or paclitaxel + gemcitabine), 17 , 18 or rechallenge of first‐line therapy.…”
Section: Methodsmentioning
confidence: 99%